UV‐B signalling in rice: Response identification, gene expression profiling and mutant isolation. (11th January 2021) - Idris, Muhammad; Seo, Nobu; Jiang, Lei; Kiyota, Seiichiro; Hidema, Jun; Iino, Moritoshi
Abstract: Responses of rice seedlings to UV‐B radiation (UV‐B) were investigated, aiming to establish rice as a model plant for UV‐B signalling studies. The growth of japonica rice coleoptiles, grown under red light, was inhibited by brief irradiation with UV‐B, but not with blue light. The effective UV‐B fluences (10 −1 ‐10 3 μmol m −2 ) were much lower than those reported in Arabidopsis. The response was much less in indica rice cultivars and its extent varied among Oryza species. We next identified UV‐B‐specific anthocyanin accumulation in the first leaf of purple rice and used this visible phenotype to isolate mutants. Some isolated mutants were further characterized, and one was found to have a defect in the growth response. Using microarrays, we identified a number of genes that are regulated by low‐fluence‐rate UV‐B in japonica coleoptiles. Some up‐regulated genes were analysed by real‐time PCR for UV‐B specificity and the difference between japonica and indica . More than 70% of UV‐B‐regulated rice genes had no homologs in UV‐B‐regulated Arabidopsis genes. Many UV‐B‐regulated rice genes are related to plant hormones and especially to jasmonate biosynthetic and responsive genes in apparent agreement with the growth response. Possible involvement of two rice homologs of UVR8, a UV‐B photoreceptor, is discussed. Abstract : Rice responds to UV‐B, as seen in coleoptile growth inhibition, much more sensitively than Arabidopsis and with UV‐B‐regulated genes largely different from Arabidopsis ones. UV‐B response mutants can be isolated from purple rice. Rice will serve as a new model plant for UV‐B signalling studies.